ECOLOGICAL HUMANISM - FROM PRIMITIVE MAN TO SUSTAINABLE DEVELOPMENT - SOBCZYK, Wiktoria (Trends in education, 2013)
For thousands of years the man has been changing the world and has been repressing the forces of nature. Human behaviour has led to a serious ecological imbalance, the harmful consequences of which can be felt across the planet. The man has a obligation to reduce threats to nature, with particular solicitude for the environment. This is achieved by the idea of sustainable development.
Keywords: man; environment; technology; sustainable development